The Specific Features of the Contemporary Russian Foreign Energy Policy Shift in Modern Times - E. S. Leonov (MGIMO University Press, 2015)
In recent years there has been brewing up a necessity in Russia to change direction of its external energy policy radically as a result of unconstructive and hugely politically charged approach of the EU - main and traditional partner of Russia - to settlement of fundamental issues in bilateral cooperation. First of all this refers to failed efforts to create regional energy security system, based on respective institutions and legal framework, by reason of unwillingness of the EU to respect the Russian standpoint as an exporter of energy resources. As a result, there is a legal vacuum today in energy cooperation between Russia and the EU, which they failed to fill. The current political crisis in Europe, which is caused by accession of the Republic of Crimea to the Russian Federation and events in Ukraine, has aggravated long-standing problems of energy partnership EU-Russia. At the same time active EU policy on diversification of energy sources and supply routes discredits peculiar role of Russia as EU key energy supplier. These factors have triggered a significant revision of Russian interests in favor of eastern direction. A new promising contract with China on 21 May 2014 and memorandum with Turkey on 1 December 2014 are the milestones of the present Russian eastern policy. Both contracts can disrupt power balance on the global energy market. The article deals with background and causes for the present Russian eastern activity.